MARIGINALISASI GENDER DALAM TEKS SATUA TANTING MAS DAN TANTING RAT - Ida Bagus Gede Paramita (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2022)
The purpose of this study is to examine the gender marjinalization in the texts of the satua Bali Tanting Mas and Tanting Rat. The aspect studied in this article is the relationship between text and context, the characters contained in the unit are seen as aspects of ideology, power and how things are in today's society. The method used in this research is qualitative method. Primary data was obtained from the text of the